Implementasi Model Discovery Learning Untuk Meningkatkan Keaktifan Siswa Pada Materi Ekosistem Kelas V SDN Sekemendung 1 - Siti Nur Aini Fajrin; Mohamad Yudiyanto; Annisa Mayasari; Jonaidi (Prodi PGMI STAI Sabili Bandung, 2022)
This research is motivated by observational data which shows that the acquisition of learning outcomes and student activity in Natural Science subjects is very low. To respond to this, the researchers conducted classroom action research that aims to improve learning outcomes and student activity. The objectives to be achieved for this research include: (1) Knowing the implementation of audio-visual media in improving student learning outcomes, (2) Knowing the increase in student activity with the Discovery Learning model in students. This research is a classroom action research with Kemmis and Mc. Taggart. The method used in this research is classroom action research with the Discovery Learning model with audio-visual media. This research was conducted in class V with 35 students at SDN Sekemandung 1. The results of the identification of the data obtained, it can be concluded that the activeness of students in learning science in the material